Ecological risk of heavy metals in sediment of an urban river in Bangladesh. Issue 3 (3rd April 2018) - Islam, Md. Saiful; Proshad, Ram; Ahmed, Saad
ABSTRACT: Levels of heavy metals, i.e., chromium (Cr), nickel (Ni), copper (Cu), arsenic (As), cadmium (Cd), and lead (Pb) in surface sediment of Buriganga River, Bangladesh were investigated to assess ecological risk. The mean concentration of Cr, Ni, Cu, As, Cd, and Pb in sediments was 297, 240, 280, 21, 7.7, and 731 mg/kg, respectively. Certain indices, including the enrichment factor (EF), pollution load index (PLI), and contamination factor were used to assess the ecological risk. The mean range of PLI was 2.9 to 13 during winter and 2.4 to 11 during summer season, indicating progressive deterioration of sediment due to metal contamination. The sum of toxic units (∑TUs) for all the sampling sites was greater than 4, indicating a moderate to serious toxicity of heavy metals in sediment. However, the values of Cd ranging from 6.7 to 61 revealed that the examined sediments were strongly impacted by Cd. Considering the severity of potential ecological risk for single metal, the descending order of contaminants was Cd > Pb > Cu > Ni > As > Cr. In view of the potential ecological risk, sediments of Buriganga River showed considerable to very high potential ecological risk.